Compatibility of Cats With Children in the Family - Hart, Lynette A.; Hart, Benjamin L.; Thigpen, Abigail P.; Willits, Neil H.; Lyons, Leslie A.; Hundenski, Stefanie (Frontiers in Veterinary Science, 2018)
Although studies involving pet dogs and cats, and human adults and children, have been reported, the specific interactions between cats and children have not. This study sought information from parents about the cat’s role in families that have at least one child 3-12 years of age and at least one cat. Demographic data on cat source, breed, gender/neuter status, was sought as well as information on adults and children in the families and on affectionate, aggressive, fearful, and playful responses of the cats to children. A convenience sample was recruited via listservs for pet owners and parents. Using a pilot tested web survey, descriptive statistics were based on 865 respondents. Multi-variate statistical analyses were conducted on data from 665 respondents with complete responses for all items, including respondents’ locations and whether cats were adopted as kittens. Multi-variate analyses included consideration of demographic data, geographic region of respondents, behavioral characteristics of the cats, and responses of the children to the cats. From descriptive statistics, cats’ affection was more typical with adults than young children. Neuter status or gender was unrelated to cats’ aggression or affection. Being the family’s only cat was associated with heightened aggression and reduced affection. Younger cats were more likely to be affectionate. Multivariate analysis revealed three primary factors accounting for children’s compatibility with the specified cat: positive interactions of the cat, aggression/fearfulness of cat, and the cat’s playfulness and children’s reaction to the cats. Positive child-cat relationships were more typical with two or more adults and multiple cats in the home. Old cats were the least satisfactory. A breeder or shelter was a better source than as a feral, from a newspaper ad, or another source. European respondents rated their cats’ interactions with children more favorably than in U.S./Canada. This difference may reflect the European adoptions more frequently being of kittens, often purebred, assuring more early handling within the family. A noteworthy finding was that all family participants, humans and pets alike, affect the cat-child relationship, and these results reveal that many variables can play a role in achieving a desirable relationship for a cat and child.